Local subcutaneous lidocaine injection for the treatment of complex regional pain syndrome: a case report and literature review - Su, Yaping; Li, Zhenyu; Wang, Qian; Tang, Hui (Frontiers in Neurology, 2023)
A 14-year-old child was diagnosed with complex regional pain syndrome (CRPS) after bromhidrosis surgery. She experienced a prickle-like, knife-like, and intermittent attacks pain, accompanied by numbness of both upper limbs and a limited movement.Ultrasound-guided radiofrequency surgery on peripheral nerve did not reduce pain.Then gabapentin 300mg, three times a day, and 2% lidocaine by local subcutaneous injection, once a day for 3 days, were administrated. After local injection subcutaneous of lidocaine, the pain was significantly relieved and the pain induced by skin touch at the scar disappeared. No pain recurred after 1-month follow-up. An evidence-based literature review showed that local or systemic intravenous lidocaine was used to reduce adult CRPS symptoms, but less has been reported in children. In our case, a local subcutaneous injection of 2% lidocaine in a child for CRPS treatment was reported to be effective in relieving complex local pain with favorable outcomes.Though further high-quality randomized controlled trials are needed to investigate the effects and safety of local subcutaneous lidocaine injection on pain relief in children with CRPS, it could still provide a relatively safe and effective adjuvant therapy for minor patients.